(untitled) (Zia e Tahqeeq, 2025)
Islamic teachings encourage Muslims to provide loans to a needy person. The Qur’an and the Sunnah have prohibited the lender from charging the borrower any additional amount. It is suggested by Islamic banks that the client, when entering into a Murabahah transaction, should undertake that in case he defaults in payment at the due date, he will pay a specified amount to a charitable fund maintained by the bank. It must be ensured that no part of this amount shall form part of the income of the bank. However, the bank may establish a charitable fund for this purpose and all amounts credited therein shall be exclusively used for purely charitable purpose approved by the Shariah. The bank may also advance interest-free loans to the needy persons from this charitable fund. It is explicitly stated that there is no concept of penalty in Islam in financial arrangements/ commitments but as per the need in Islamic financial sector it is mandatory to fix a certain penalty to discourage the malpractices of delay in payments or willful defaults by the clients. The real solution to this problem is to develop a system where the defaulters are duly punished by depriving them from enjoying a financial facility in future.